A boundary-discontinuous-displacement based Fourier analysis of thick laminated beams via a robust 1D-CUF model. (July 2017) - Canales, FG; Mantari, JL
Abstract: This paper presents an analytical solution for the static analysis of thick laminated rectangular beams with clamped boundary conditions at either or both of the beam's edges. A unified formulation known as Carrera's Unified Formulation (CUF) is used in order to consider shear deformation theories of arbitrary order. The governing equations are obtained by using the principle of virtual work. The main novelty is the use of the boundary-discontinuous Fourier approach for laminated beams in the framework of a unified formulation. Unlike Navier-type solutions, the present development can obtain analytical solutions for beams with clamped boundary conditions. A 3D finite element solution is used to validate the obtained results. The present theory can analyze clamped beams accurately so benchmark results are provided.